PROMOTING EFFECTIVE FINANCIAL ACCOUNTABILITY IN LOCAL GOVERNMENT IN THE NORTH WEST PROVINCE: DEVELOPING OPERATIONAL GUIDELINES FOR MUNICIPAL PUBLIC ACCOUNTS COMMITTEES - BOTLHOKO, THELO STEPHEN (Bloemfontein: Central University of Technology, Free State, 2017)
Political reform as set out in sections 40 (1) (2) and 41 of the Constitution, 1996 of South Africa has been one of the most important factors leading to the democratization of state institutions. This move has further contributed to the decentralization of the public service. It is, however, concerning that since 1995 local government has been faced with enormous challenges in its pursuit of providing quality services and effective governance. Municipal councils in South Africa are vested with the legislative responsibility to promote sound financial management practices. Despite the institutional mechanisms that have been established to prevent fraud, corruption and other forms of lawless practices, the non-compliance with legislation impacted negatively on the performance of most of the municipalities. The municipalities incurred unauthorized, irregular as well as fruitless and wasteful expenditures. These expenditures were also expended by municipalities during the previous financial years and were never investigated. The Local Government: Municipal Finance Management Act, 2003 (Act 56 of 2003) (MFMA), the Local Government: Municipal Structures Act,1998 (Act 117 of 1998)(hereafter referred to as the Municipal Structures Act), the Local Government: Municipal Systems Act, 2000 (Act 32 of 2000)(hereafter referred to as the Municipal Systems Act) and other relevant legislation and regulations have been critically analysed to determine whether municipalities in the North West Province comply with the principles of good governance. The following reports of the Auditor-General of South Africa (AGSA) indicate a declining pattern in the financial management of municipalities in South Africa. The 2006/07 report of the AGSA indicates that 78% of the municipalities in the North West Province had the highest levels of adverse and disclaimer opinions. In the 2008/09 audit report, the AGSA expressed the concern that 110 of the 163 municipalities that received a qualified opinion did not address the audit findings. The AGSA pointed out in his/her 2010/11 report that the audit outcomes had not shown the required improvements. The report stated that only 13 of the 283 municipalities across the country received an unqualified opinion. The 2011/12 report of the AGSA paints a grim picture of the state of municipalities, with only 5% of the 278 receiving a clean audit opinion. The report stated that the majority of municipalities which showed poor audit outcomes were from the North West Province. The research study established that in most of the municipalities a lack of culture regarding accountability, political crisis, and a lack of relevant capacity at some of the municipalities in the North West Province impacted negatively on the improvement of governance. The lack of clearly defined roles and the responsibilities of the MPACs compromised the oversight function. The AGSA in his/her report expressed concern about such practice and pointed out that if the situation was not urgently attended to it would further contribute to an environment susceptible to a breakdown in significant key controls and consequently result in the total collapse of good governance. The MEC for Local Government and Traditional Affairs placed 8 of the municipalities under section 137(1)(b) of the Constitution, 1996. One of the 8 municipalities was a district municipality, which was later placed under section 139(1)(c) of the Constitution, 1996. This mandatory provincial intervention was implemented as a result of serious and persistent financial crises and the material breach of obligations by the municipalities. The situation did not improve despite this action by the MEC, but rather regressed after the lifting of the intervention. Sections 33 and 79 of the Municipal Structures Act require that municipalities should establish oversight committees that are responsible for the detailed analysis and review of the annual reports. In terms of the Act, a Municipal Public Accounts Committee (MPAC) must be established to exercise oversight over the obligations of the municipal council. The mandate of the committee is drawn from sections 55 and 114 of the Constitution, 1996. This research study focussed on developing operational guidelines for Municipal Public Accounts Committees (MPACs) to promote effective financial accountability for local government in the North West Province. A total number of 15 municipalities that constitute 65% of the municipalities in the province were selected as a case study. A comprehensive literature study of the topic, including national and international books, journals, acts and various sources of legislation, research reports, government documents and newspaper articles served as the primary source of data collection. A format of in-depth and semi-structured interviews was conducted with specific role- players as part of the identified population who were the most important participants and have contributed to and ratified the reliability and quality of the research outcome. The respondents were selected in a purposive manner by targeting key informants who, on account of their positions and experience, have more information than ordinary potential respondents. The study concluded that all the challenges that prevent the smooth functioning of the municipalities in the North West Province must be resolved by implementing the legislation that is relevant and applicable to local government. The study recommended that operational guidelines for the MPACs to promote effective financial accountability at all the municipalities in the North West Province must be developed. The operational guidelines will assist the MPAC to execute its work when: ● Reviewing the reports of the AGSA and those of the Audit Committee; ● Planning and conducting meetings of the committee; ● Planning and conducting public hearings; ● Developing MPAC reports; ● Following up on the recommendations of the MPAC and ● Measuring the performance of the MPAC.
Published Thesis